SITE SUITABILITY ANALYSIS FOR CROP MAPPING USING GEOSPATIAL TECHNIQUES IN AKKO LGA, GOMBE STATE - ABUBAKAR, AISHA SHUAIBU; MUHAMMAD , MUSTAPHA IBRAHIM; JIBRIL , ABUBAKAR BABAYO (Int'l Journal of Education Research and Scientific Development, 2024)
Land suitability analysis is a prerequisite for sustainable agricultural production. This study is aimed at evaluating the current physical land suitability for rice, maize and soya beans in Akko local government area, Gombe state, Nigeria. A GIS and RS technique with a multicriteria evaluation approach are applied for evaluating the physical land suitability for the mentioned crops. To achieve this, fifteen parameters were considered which constitute topographic, climatic and physiochemical factors. The acquired data were spatially processed and analyzed through vector to raster conversion, raster coordinates transformation and resampling, criteria standardization and weighting and; finally integrated to three suitability maps each for the selected crop. The results shows that areas that are highly and moderately suitable for maize, rice and soya beans crops cultivation are ascertained as 53.57%, 21.33% and 49.39% respectively of the total LGA’s area; this corresponds to 1,410.12 Km², 549.59 Km² and 1,272.56 Km² respectively. These findings indicate that there are considerable suitable lands with huge potential for optimal yield production for the selected crops in Akko LGA. The findings should be put into use by local and state agricultural extension officers, which will serves as vital tool in directing farmers on what to grow on which land for optimum yield production. Hence, this would enhance crops productivity in a sustainable manner and improve food security for better socio-economic development of Akko LGA and Gombe states at large.